Fibre Multi-Object Spectrograph (FMOS) for the Subaru Telescope - Kimura, M; Maihara, T; Iwamuro, F; Akiyama, M; Tamura, N; Dalton, G; Takato, N; Tait, P; Ohta, K; Eto, S; Mochida, D; Elms, B; et al. (Astronomical Society of Japan, 2010)
Fibre Multi-Object Spectrograph (FMOS) is the first near-infrared instrument with a wide field of view capable of acquiring spectra simultaneously from up to 400 objects. It has been developed as a common-use instrument for the F=2 prime-focus of the Subaru Telescope. The field coverage of 300 diameter is achieved using a new 3-element corrector optimized in the near-infrared (0.9-1.8μm) wavelength range. Due to limited space at the prime-focus, we have had to develop a novel fibre positioner, called " Echidna" , together with two OH-airglow suppressed spectrographs. FMOS consists of three subsystems: the prime focus unit for IR, the fibre positioning system/connector units, and the two spectrographs. After full systems integration, FMOS was installed on the telescope in late 2007. Many aspects of the performance were checked through various test and engineering observations. In this paper, we present the optical and mechanical components of FMOS, and show the results of our on-sky engineering observations to date. © 2010. Astronomical Society of Japan.